Coping Behaviors and Psychological Disturbances in Youth Affected by the COVID-19 Health Crisis - Orgilés, Mireia; Morales, Alexandra; Delvecchio, Elisa; Francisco, Rita; Mazzeschi, Claudia; Pedro, Marta; Espada, José Pedro (Frontiers in Psychology, 2021)
The COVID-19 pandemic and the quarantine undergone by children in many countries is a stressful situation about which little is known to date. Children and adolescents' behaviors to cope with home confinement may be associated with their emotional welfare. The objectives of this study were: (1) to examine the coping strategies used out by children and adolescents during the COVID-19 health crisis, (2) to analyze the differences in these behaviors in three countries, and (3) to examine the relationship between different coping modalities and adaptation. Participants were 1,480 parents of children aged 3–18 years from three European countries (nSpain = 431, nItaly = 712, and nPortugal = 355). The children's mean age was 9.15 years (SD = 4.27). Parents completed an online survey providing information on symptoms and coping behaviors observed in their children. The most frequent coping strategies were accepting what is happening (58.9%), collaborating with quarantine social activities (e.g., drawings on the windows, supportive applauses) (35.9%), acting as if nothing is happening (35.5%), highlighting the advantages of being at home (35.1%), and not appearing to be worried about what is happening (30.1%). Compared to Italian and Spanish children, Portuguese children used a sense of humor more frequently when their parents talked about the situation. Acting as if nothing was happening, collaborating with social activities, and seeking comfort from others were more likely in Spanish children than in children from the other countries. Compared to Portuguese and Spanish children, Italian children did not seem worried about what was happening. Overall, an emotional-oriented coping style was directly correlated with a greater presence of anxious symptoms, as well as to mood, sleep, behavioral, and cognitive alterations. Task-oriented and avoidance-oriented styles were related to better psychological adaptation (considered a low presence of psychological symptoms). Results also show that unaffected children or children with a lower level of impact were more likely to use strategies based on a positive focus on the situation. This study provides interesting data on the strategies to be promoted by parents to cope with the COVID-19 health crisis in children.